2006
DOI: 10.1007/s11106-006-0105-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria in the system HfO2-ZrO2-CeO2 at 1500°C

Abstract: UDC 621.762 Phase equilibria in the ternary system HfO 2 − ZrO 2 − CeO 2 at 1500°C are studied for the first time over the whole concentration range and an isothermal section of the phase equilibrium diagram at this temperature is constructed. Specimens of different compositions, synthesized from nitrate solutions by evaporation, drying, and heat treatment at 1500°C, are studied by x-ray phase and petrographic analyses, and by electron microscopy. Three regions are established for solid solutions with a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
3
9
0
2
Order By: Relevance
“…This finding is in agreement with previous work on the thermally induced transformations in the CeO 2 -Y 2 O 3 system[28], demonstrating that the maximum solubility of Y 2 O 3 in CeO 2 (sometimes called "hot spots" or "thermal spikes"[29]) occurred during highenergy ball milling provide important factors enhancing the reaction between CeO 2 and Y 2 O 3 reactants.Fig. 1 (bottom)shows the XRD pattern of the mechanosynthesized Ce 0.65 Y 0.35 O 2-δ phase after thermal treatment at 800°C for 4 h in ambient atmosphere.…”
supporting
confidence: 92%
“…This finding is in agreement with previous work on the thermally induced transformations in the CeO 2 -Y 2 O 3 system[28], demonstrating that the maximum solubility of Y 2 O 3 in CeO 2 (sometimes called "hot spots" or "thermal spikes"[29]) occurred during highenergy ball milling provide important factors enhancing the reaction between CeO 2 and Y 2 O 3 reactants.Fig. 1 (bottom)shows the XRD pattern of the mechanosynthesized Ce 0.65 Y 0.35 O 2-δ phase after thermal treatment at 800°C for 4 h in ambient atmosphere.…”
supporting
confidence: 92%
“…It is also known that Ce may enhance the stability of the cubic phase [54,55]. However, the HfO2-CeO2-ZrO2 ternary phase diagram shows the three-phase region (monoclinic + tetragonal + cubic) for the equimolar composition at 1500°C [56]. It appears that the cubic stabilizers in this system affects the phase stability to a more considerable degree in this CCFO system than yttria does in the zirconia system.…”
Section: Phase Stabilitymentioning
confidence: 81%
“…All specimens were annealed at the respective temperatures for 24 h and subsequently quenched. The composition (Hf1/3Zr1/3Ce1/3)O2 exhibits three phases according to Andrievskaya et al[56]. (Legends: ▲ = 3 phase; • = tetragonal; ■ = cubic.)…”
mentioning
confidence: 99%
“…the system appears to be fully miscible in the entire composition range as already reported by several authors. 27,29,31,55,56 In contrast, Sammes et al 57 found a local maximum of the cell parameter vs. x in the system (CeO 2 ) 1Àx (8YSZ) x for x E 0.5 and drew the conclusion that CeO 2 has a limited solubility in YSZ. Similar results from Hinatsu et al 58 and Sakai et al 53 indicate a miscibility gap for In addition to phase analysis by X-ray diffraction (XRD), Raman spectroscopy on small single crystals of each composition was performed (Fig.…”
Section: Phase Analysis and Compositionmentioning
confidence: 99%